(untitled) (International Journal of Engineering and Computer Science, 2015)
Wireless sensor network has many application such as environment sensing, building safety monitoring, earthquake prediction etc. Security is critical issue in sensor networks. A fundamental security service is to establish pairwise key shared between two sensor nodes, which is basis of other security such as encryption and authentication. The prime problem in key management is to establish secure keys between the sensor nodes. To avoid this pairwise key establishment is used. This scheme consists of two key pools. One key pool is hashed value of keys in another key pool. With the one-way hash function, this scheme can make attackers get less key information from the compromised sensor nodes. Along with this Otway Rees protocol is used to provide integrity and authenticity. If direct path between two sensors are not present, then by using this protocol it is easy to find key with the help of intermediate node.